2023
DOI: 10.3390/nu15143084
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Low-Carbohydrate Diets and Low-Fat Diets with Frailty in Community-Dwelling Aging Chinese Adults

Abstract: Frailty is a major health issue associated with aging. Diet affects frailty status; however, studies on the associations between the low-carbohydrate diet (LCD) score, low-fat diet (LFD) score and frailty in older Chinese adults are scarce. This study aimed to examine the associations between the LCD score, LFD score and risk of frailty in older Chinese adults. We analyzed data from 6414 participants aged ≥ 60 years from the China Northwest Natural Population Cohort: Ningxia Project. Frailty was measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The types of foods consumed were generally lacking diversity and the main energy sources were rice and noodles. A cross-sectional study in northwest China found that a high-carbohydrate diet was associated with a higher risk of frailty and pre-frailty [ 32 ]. This may account for part of the vast regional difference.…”
Section: Discussionmentioning
confidence: 99%
“…The types of foods consumed were generally lacking diversity and the main energy sources were rice and noodles. A cross-sectional study in northwest China found that a high-carbohydrate diet was associated with a higher risk of frailty and pre-frailty [ 32 ]. This may account for part of the vast regional difference.…”
Section: Discussionmentioning
confidence: 99%